Sistem Informasi Kepuasan Pelanggan Terhadap Layanan Di Pasar Gelugur Rantauprapat Berbasis Web Menggunakan Framework Codeigniter - Ilham Taufiq (Journal of Student Development Information System (JoSDIS), 2021)
Writing this Final Task aims to qualify for the approval of diploma 3 Informatics Management program with the title "Customer Satisfaction Information System Against Services In Gelugur Rantauprapat Web-Based Market Using Codeigniter Framework" which aims to know how much satisfaction level of service has been provided by the market to customers through computerized information systems.